Building Lecturer Performance Through Organizational Culture and Work Motivation - Rusmini Rusmini (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2021)
The study aims to test hypotheses and analyze organizational culture and work motivation influences on the performance of lecturers at the Islamic Education Management Study Program, Faculty of Tarbiyah and Teacher Training, UIN Sulthan Thaha Saifuddin Jambi. This research is a quantitative study, with a survey method with path analysis techniques, namely R Square analysis, testing the partial hypothesis with the t test and simultaneously with the F test, with an alpha of 5% (0.05). The total population are 30 lecturers. Data analysis was performed using SPSS version 20.0. The results showed that there was a positive and significant influence between organizational culture and work motivation variables on lecturer performance, either partially or simultaneously.